Direct Observation of Shallow Trap States in Thermal Equilibrium with Band‐Edge Excitons in Strongly Confined CsPbBr3 Perovskite Nanoplatelets. Issue 1 (8th November 2020) - Socie, Etienne; Vale, Brener R. C.; Burgos‐Caminal, Andrés; Moser, Jacques‐E.
Abstract: Lead halide perovskites exhibit great potential for light‐emitting devices. Enhanced photoluminescence (PL) is obtained in perovskite materials of reduced dimensionalities due to the large exciton binding energy. However, as the nanocrystal size is reduced, the surface‐to‐volume ratio increases, leading to an abundance of surface defects. Here, a fast PL decay, 3–10 ps, is observed in quasi‐1D CsPbBr3 perovskite nanoplatelets using broadband fluorescence upconversion spectroscopy. This decay is attributed to reversible trapping of band‐edge excitons into dark states that lie close to the band edge. A simplified model is proposed to further confirm the presence of shallow traps and to fit the data obtained by ultrafast spectroscopy for multiple samples. Finally, the presence of deep trap states in aged nanoplatelets is revealed, likely arising from desorption of the organic capping ligands from the surface. Exciton trapping into these states is slower, 20–30 ps, but leads to a decrease in the photoluminescence quantum yield. These results may not only explain the extended luminescence lifetimes that have been reported for perovskite nanocrystals but also demonstrate the potential of combining ultrafast transient absorption and fluorescence up‐conversion to obtain a full description of the spectroscopic properties of the material. Abstract : CsPbBr3 nanoplatelets are promising materials for light generation thanks to a large exciton binding energy and high radiative rates. A single intrinsic shallow trap state is evidenced in fresh samples by application of transient absorption and fluorescence up‐conversion spectroscopies. Reversible band‐edge exciton localization in this state takes place in the picosecond time scale without undermining the emission quantum efficiency.